2022
DOI: 10.1021/acsami.2c16856
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Nickel Phthalocyanine-Based Electrochemical CNT Sponges for Ammonia Synthesis from Nitrate in Contaminated Water

Abstract: Electrochemical reduction of nitrate to ammonia is of great interest in water treatment with regard to the conversion of contaminants to value-added products, which requires the development of advanced electrodes to achieve high selectivity, stability, and Faradaic efficiency (FE). Herein, nickel phthalocyanine was homogeneously doped into the fiber of a carbon nanotube (CNT) sponge, enabling the production of an electrode with high electrochemical double-layer capacitance (C DL) and a large electrochemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Cobalt and copper phthalocyanines (CoPc, CuPc) anchored on carbon nanotubes electrochemically convert nitrate to ammonia with higher activity and selectivity than aggregated Pc samples. [77][78][79] The CNT-supported CuPc material is 30% more active than the carbon black-supported CuPc. 77 CuPc requires a lower NO 3 − reduction overpotential (η) compared to the cobalt analog to reach a j of 10 mA cm −2 and a faradaic efficiency (FE) over 98%.…”
Section: Nitrate/nitrite Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cobalt and copper phthalocyanines (CoPc, CuPc) anchored on carbon nanotubes electrochemically convert nitrate to ammonia with higher activity and selectivity than aggregated Pc samples. [77][78][79] The CNT-supported CuPc material is 30% more active than the carbon black-supported CuPc. 77 CuPc requires a lower NO 3 − reduction overpotential (η) compared to the cobalt analog to reach a j of 10 mA cm −2 and a faradaic efficiency (FE) over 98%.…”
Section: Nitrate/nitrite Reductionmentioning
confidence: 99%
“…NiPc-CNT sponges achieve 98% nitrate removal after 4 h of electrolysis due to the high electrochemically active surface area (ECSA) layer of the CNT sponge. 78 CoPc has the overall highest performance for nitrate reduction, with an ammonia conversion rate >97%. 79 75 At acidic pH values, hydroxylamine is the main product at 100% selectivity with the Co-PP system.…”
Section: Nitrate/nitrite Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen in nitrate ions has an oxidation state of +5, which can form a number of nitrogenous products in oxidation states from +3 to −3, including nitrite (+3, NO 2 – ), nitric oxide (+2, NO), nitrous oxide (+1, N 2 O), nitrogen (0, N 2 ), hydroxylamine (−1, NH 2 OH), hydrazine (−2, N 2 H 4 ), and ammonia (−3, NH 3 ). , Development of numerous electrocatalytic systems using a variety of heterogeneous catalysts including Cu, Ag, Au, Rh, Ru, Ir, Pd, Pt, etc. often converts NO 3 – to N 2 via a five-electron transfer process. Several research groups have also shown that electrochemically NO 3 – can be converted to hydroxylamine, nitrite, and hydrazine. Electrocatalytic nitrate to ammonia conversion [NO 3 – + 6H 2 O + 8e – → NH 3 + 9OH – ] via an eight-electron transfer process using metal, nonmetal, and transition-metal-based electrocatalysts would be an alternative option for next-generation ammonia production. The selectivity toward ammonia synthesis was unsatisfactory, and generally a broad range of products is obtained. This is due to the complexity of the process, strong competition from HER, and the production of various byproducts, which reduce the faradaic efficiency (FE) and selectivity of ammonia .…”
Section: Introductionmentioning
confidence: 99%